Determinants of full immunization coverage among children 12–23 months of age from deviant mothers/caregivers in Ethiopia: A multilevel analysis using 2016 demographic and health survey - Mihret Fetene, Samrawit; Debebe Negash, Wubshet; Shewarega, Ever Siyoum; Asmamaw, Desale Bihonegn; Belay, Daniel Gashaneh; Teklu, Rediet Eristu; Aragaw, Fantu Mamo; Alemu, Tewodros Getaneh; Eshetu, Habitu Birhan; Fentie, Elsa Awoke (Frontiers in Public Health, 2023)
Background: Despite remarkable improvements in child health services utilization, childhood immunization has been poorly implemented in Ethiopia. However, evidence on the coverage of immunization among children from mothers/caregivers with no education (non-educated mothers were the most identified risk for underutilization of services) are scarce. Therefore, this study aimed to assess the determinants of full immunization coverage among children 12-23 months of age from deviant mothers/caregivers in Ethiopia. Methods: We analyzed data from the 2016 Ethiopia Demographic and Health Survey (EDHS) on a sample of 1170 children 12-23 months of age identified from deviant mothers/caregivers (mothers/caregivers with no education) through a two-stage stratified sampling. A multilevel mixed-effect binary logistic regression analysis was used to identify the individual and community level determinants of full immunization coverage among children 12-23 months of age with their deviant mothers/caregivers. In the final model, a p-value of less than 0.05 and adjusted odds ratio (AOR) with 95% confidence interval (CI) were used to select statistically significant determinants of full immunization coverage. Results: The overall full immunization coverage among children 12-23 months of age from deviant mothers/caregivers was 27.4% (95%CI: 25.0, 31.0) in Ethiopia. Deviant mothers/caregivers who are employed (AOR=1.69, 95%CI: 1.68, 2.45), being in the rich household wealth status (AOR=2.54, 95%CI: 1.53, 4.22), residing in city (AOR=5.69, 95%CI: 2.39, 13.61), having one to three (AOR: 3.28, 95% CI: 2.12-5.07) and four and more ANC follow-up during the recent pregnancy (AOR: 3.91, 95% CI: 2.45, 6.24) were the determinants that increased full immunization coverage among children 12-23 months of age. Conclusions: Full immunization coverage among children 12-23 months of age from non-educated mothers/caregivers was low and far behind the national target of coverage. Therefore, a system-wide intervention should be used to enhance employability, wealth status, and key maternal health services like ANC follow-up among non-educated mothers/caregivers to increase their children’s full immunization coverage.